2017
DOI: 10.1177/1847979017712629
|View full text |Cite
|
Sign up to set email alerts
|

Using social network analysis to identify stakeholders’ influence on energy efficiency of housing

Abstract: Energy-efficient housing is a product that integrates various stakeholders' tasks throughout the different stages of its life cycle. The relationships between these stakeholders impact on the degree of knowledge sharing and informed decisionmaking and can potentially enhance or lower the energy efficiency of the product -the house. This article uses a social network analysis (SNA) approach to visualize the social networks of the stakeholders of a number of owner-occupied housing case studies in Australia. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 49 publications
(92 reference statements)
0
35
0
4
Order By: Relevance
“…Faced with this panorama, various researchers recognize the importance of an in-depth analysis of the relationships between stakeholders (ROWLEY and MOLDOVEANU, 2003;ROLOFF, 2008;GARRIGA, 2009;ZENG, CHEN, DONG et al, 2015;CABRAL, FERNANDES and RIBEIRO, 2016;ZEDAN and MILLER, 2017;YANG and BENTLEY, 2017). They suggest social network analysis to evaluate how the structure of the stakeholder network and the position of each stakeholder within that structure can influence the organization.…”
Section: The Stakeholder Network Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Faced with this panorama, various researchers recognize the importance of an in-depth analysis of the relationships between stakeholders (ROWLEY and MOLDOVEANU, 2003;ROLOFF, 2008;GARRIGA, 2009;ZENG, CHEN, DONG et al, 2015;CABRAL, FERNANDES and RIBEIRO, 2016;ZEDAN and MILLER, 2017;YANG and BENTLEY, 2017). They suggest social network analysis to evaluate how the structure of the stakeholder network and the position of each stakeholder within that structure can influence the organization.…”
Section: The Stakeholder Network Approachmentioning
confidence: 99%
“…The contributions of the empirical articles were analyzed and it was observed that three of these studies seek to apply and expand the model from Rowley (1997). The empirical studies are those of Garriga (2009), Fassin, Colle andFreeman (2017), and Zedan and Miller (2017). The choice of empirical articles is warranted here due to the objective of this study being to reveal the stakeholder networks approach as practice, aiming to understand how it has developed empirically in the last 20 years, that is, since it was proposed.…”
Section: Figure 5 Abstract Clustermentioning
confidence: 99%
See 2 more Smart Citations
“…The contributions of the empirical articles were analyzed and it was observed that three of these studies seek to apply and expand the model from Rowley (1997). The empirical studies are those of Garriga (2009), Fassin, Colle and Freeman (2017), and Zedan and Miller (2017). The choice of empirical articles is warranted here due to the objective of this study being to reveal the stakeholder networks approach as practice, aiming to understand how it has developed empirically in the last 20 years, that is, since it was proposed.…”
Section: Figure 5 Abstract Clustermentioning
confidence: 99%